5.9.26 Problems 2501 to 2600

Table 5.679: First order ode linear in derivative

#

ODE

Mathematica

Maple

5873

\[ {}\left (3 x +2 y+1\right ) y^{\prime }+4 x +3 y+2 = 0 \]

5874

\[ {}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y \]

5875

\[ {}y+\left (1+y^{2} {\mathrm e}^{2 x}\right ) y^{\prime } = 0 \]

5876

\[ {}x^{2} y+y^{2}+x^{3} y^{\prime } = 0 \]

5877

\[ {}y^{2} {\mathrm e}^{x y^{2}}+4 x^{3}+\left (2 x y \,{\mathrm e}^{x y^{2}}-3 y^{2}\right ) y^{\prime } = 0 \]

5878

\[ {}y^{\prime } = \left (x^{2}+2 y-1\right )^{{2}/{3}}-x \]

5879

\[ {}x y^{\prime }+y = x^{2} \left (1+{\mathrm e}^{x}\right ) y^{2} \]

5880

\[ {}2 y-x y \ln \left (x \right )-2 x \ln \left (x \right ) y^{\prime } = 0 \]

5881

\[ {}y^{\prime }+a y = k \,{\mathrm e}^{b x} \]

5882

\[ {}y^{\prime } = \left (x +y\right )^{2} \]

5883

\[ {}y^{\prime }+8 x^{3} y^{3}+2 x y = 0 \]

5884

\[ {}\left (x y \sqrt {x^{2}-y^{2}}+x \right ) y^{\prime } = y-x^{2} \sqrt {x^{2}-y^{2}} \]

5885

\[ {}y^{\prime }+a y = b \sin \left (k x \right ) \]

5886

\[ {}x y^{\prime }-y^{2}+1 = 0 \]

5887

\[ {}\left (y^{2}+a \sin \left (x \right )\right ) y^{\prime } = \cos \left (x \right ) \]

5888

\[ {}x y^{\prime } = x \,{\mathrm e}^{\frac {y}{x}}+x +y \]

5889

\[ {}y^{\prime }+y \cos \left (x \right ) = {\mathrm e}^{-\sin \left (x \right )} \]

5890

\[ {}x y^{\prime }-y \left (\ln \left (x y\right )-1\right ) = 0 \]

5891

\[ {}x^{3} y^{\prime }-y^{2}-x^{2} y = 0 \]

5892

\[ {}x y^{\prime }+a y+b \,x^{n} = 0 \]

5893

\[ {}x y^{\prime }-y-\sin \left (\frac {y}{x}\right ) x = 0 \]

5894

\[ {}y^{2}-3 x y-2 x^{2}+\left (x y-x^{2}\right ) y^{\prime } = 0 \]

5895

\[ {}\left (6 x y+x^{2}+3\right ) y^{\prime }+3 y^{2}+2 x y+2 x = 0 \]

5896

\[ {}x^{2} y^{\prime }+y^{2}+x y+x^{2} = 0 \]

5897

\[ {}\left (x^{2}-1\right ) y^{\prime }+2 x y-\cos \left (x \right ) = 0 \]

5898

\[ {}\left (x^{2} y-1\right ) y^{\prime }+x y^{2}-1 = 0 \]

5899

\[ {}\left (x^{2}-1\right ) y^{\prime }+x y-3 x y^{2} = 0 \]

5900

\[ {}\left (x^{2}-1\right ) y^{\prime }-2 x y \ln \left (y\right ) = 0 \]

5901

\[ {}\left (1+x^{2}+y^{2}\right ) y^{\prime }+2 x y+x^{2}+3 = 0 \]

5902

\[ {}\cos \left (x \right ) y^{\prime }+y+\cos \left (x \right ) \left (\sin \left (x \right )+1\right ) = 0 \]

5903

\[ {}y^{2}+12 x^{2} y+\left (2 x y+4 x^{3}\right ) y^{\prime } = 0 \]

5904

\[ {}\left (x^{2}-y\right ) y^{\prime }+x = 0 \]

5905

\[ {}\left (x^{2}-y\right ) y^{\prime }-4 x y = 0 \]

5906

\[ {}x y y^{\prime }+x^{2}+y^{2} = 0 \]

5907

\[ {}2 x y y^{\prime }+3 x^{2}-y^{2} = 0 \]

5908

\[ {}\left (2 x y^{3}-x^{4}\right ) y^{\prime }+2 x^{3} y-y^{4} = 0 \]

5909

\[ {}\left (x y-1\right )^{2} x y^{\prime }+\left (1+x^{2} y^{2}\right ) y = 0 \]

5910

\[ {}\left (x^{2}+y^{2}\right ) y^{\prime }+2 x \left (y+2 x \right ) = 0 \]

5911

\[ {}3 y^{2} y^{\prime } x +y^{3}-2 x = 0 \]

5912

\[ {}2 y^{3} y^{\prime }+x y^{2}-x^{3} = 0 \]

5913

\[ {}\left (2 x y^{3}+x y+x^{2}\right ) y^{\prime }-x y+y^{2} = 0 \]

5914

\[ {}\left (2 y^{3}+y\right ) y^{\prime }-2 x^{3}-x = 0 \]

5915

\[ {}y^{\prime }-{\mathrm e}^{x -y}+{\mathrm e}^{x} = 0 \]

6019

\[ {}-a y^{3}-\frac {b}{x^{{3}/{2}}}+y^{\prime } = 0 \]

6020

\[ {}a x y^{3}+b y^{2}+y^{\prime } = 0 \]

6021

\[ {}y^{\prime }-x^{a} y^{3}+3 y^{2}-x^{-a} y-x^{-2 a}+a \,x^{-a -1} = 0 \]

6022

\[ {}y^{\prime }-\left (y-f \left (x \right )\right ) \left (y-g \left (x \right )\right ) \left (y-\frac {f \left (x \right ) a +b g \left (x \right )}{a +b}\right ) h \left (x \right )-\frac {f^{\prime }\left (x \right ) \left (y-g \left (x \right )\right )}{f \left (x \right )-g \left (x \right )}-\frac {g^{\prime }\left (x \right ) \left (y-f \left (x \right )\right )}{g \left (x \right )-f \left (x \right )} = 0 \]

6023

\[ {}x^{2} y^{\prime }+x y^{3}+y^{2} a = 0 \]

6024

\[ {}\left (a x +b \right )^{2} y^{\prime }+\left (a x +b \right ) y^{3}+c y^{2} = 0 \]

6025

\[ {}y^{\prime }+\tan \left (x \right ) y = 0 \]

6029

\[ {}y^{\prime } = {\mathrm e}^{a x}+a y \]

6031

\[ {}\left (1+x \right ) y+\left (1-y\right ) x y^{\prime } = 0 \]

6032

\[ {}y^{\prime } = a y^{2} x \]

6033

\[ {}y^{2}+x y^{2}+\left (x^{2}-x^{2} y\right ) y^{\prime } = 0 \]

6034

\[ {}x y \left (x^{2}+1\right ) y^{\prime } = 1+y^{2} \]

6035

\[ {}\frac {x}{1+y} = \frac {y y^{\prime }}{1+x} \]

6036

\[ {}y^{\prime }+y^{2} b^{2} = a^{2} \]

6037

\[ {}y^{\prime } = \frac {1+y^{2}}{x^{2}+1} \]

6038

\[ {}\sin \left (x \right ) \cos \left (y\right ) = \cos \left (x \right ) \sin \left (y\right ) y^{\prime } \]

6039

\[ {}a x y^{\prime }+2 y = x y y^{\prime } \]

6075

\[ {}y^{\prime }+y^{2} = \frac {a^{2}}{x^{4}} \]

6092

\[ {}y^{\prime } = y \]

6093

\[ {}x y^{\prime } = y \]

6094

\[ {}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0 \]

6095

\[ {}\sin \left (x \right ) y^{\prime } = y \ln \left (y\right ) \]

6096

\[ {}1+y^{2}+x y y^{\prime } = 0 \]

6097

\[ {}x y y^{\prime }-x y = y \]

6098

\[ {}y^{\prime } = \frac {2 x y^{2}+x}{x^{2} y-y} \]

6099

\[ {}y y^{\prime }+x y^{2}-8 x = 0 \]

6100

\[ {}y^{\prime }+2 x y^{2} = 0 \]

6101

\[ {}\left (1+y\right ) y^{\prime } = y \]

6102

\[ {}y^{\prime }-x y = x \]

6103

\[ {}2 y^{\prime } = 3 \left (y-2\right )^{{1}/{3}} \]

6104

\[ {}\left (x +x y\right ) y^{\prime }+y = 0 \]

6105

\[ {}y^{\prime }+y = {\mathrm e}^{x} \]

6106

\[ {}x^{2} y^{\prime }+3 x y = 1 \]

6107

\[ {}y^{\prime }+2 x y-x \,{\mathrm e}^{-x^{2}} = 0 \]

6108

\[ {}2 x y^{\prime }+y = 2 x^{{5}/{2}} \]

6109

\[ {}\cos \left (x \right ) y^{\prime }+y = \cos \left (x \right )^{2} \]

6110

\[ {}y^{\prime }+\frac {y}{\sqrt {x^{2}+1}} = \frac {1}{x +\sqrt {x^{2}+1}} \]

6111

\[ {}\left (1+{\mathrm e}^{x}\right ) y^{\prime }+2 y \,{\mathrm e}^{x} = \left (1+{\mathrm e}^{x}\right ) {\mathrm e}^{x} \]

6112

\[ {}x \ln \left (x \right ) y^{\prime }+y = \ln \left (x \right ) \]

6113

\[ {}\left (-x^{2}+1\right ) y^{\prime } = x y+2 x \sqrt {-x^{2}+1} \]

6114

\[ {}y^{\prime }+y \tanh \left (x \right ) = 2 \,{\mathrm e}^{x} \]

6115

\[ {}y^{\prime }+y \cos \left (x \right ) = \sin \left (2 x \right ) \]

6116

\[ {}x^{\prime } = \cos \left (y \right )-x \tan \left (y \right ) \]

6117

\[ {}x^{\prime }+x-{\mathrm e}^{y} = 0 \]

6118

\[ {}x^{\prime } = \frac {3 y^{{2}/{3}}-x}{3 y} \]

6119

\[ {}y^{\prime }+y = x y^{{2}/{3}} \]

6120

\[ {}y^{\prime }+\frac {y}{x} = 2 x^{{3}/{2}} \sqrt {y} \]

6121

\[ {}3 y^{2} y^{\prime } x +3 y^{3} = 1 \]

6122

\[ {}2 x \,{\mathrm e}^{3 y}+{\mathrm e}^{x}+\left (3 x^{2} {\mathrm e}^{3 y}-y^{2}\right ) y^{\prime } = 0 \]

6123

\[ {}\left (x -y\right ) y^{\prime }+x +y+1 = 0 \]

6124

\[ {}\cos \left (x \right ) \cos \left (y\right )+\sin \left (x \right )^{2}-\left (\sin \left (x \right ) \sin \left (y\right )+\cos \left (y\right )^{2}\right ) y^{\prime } = 0 \]

6125

\[ {}x^{2} y^{\prime }+y^{2}-x y = 0 \]

6126

\[ {}y y^{\prime } = -x +\sqrt {x^{2}+y^{2}} \]

6127

\[ {}x y+\left (y^{2}-x^{2}\right ) y^{\prime } = 0 \]

6128

\[ {}y^{2}-x y+\left (x y+x^{2}\right ) y^{\prime } = 0 \]

6129

\[ {}y^{\prime } = \cos \left (x +y\right ) \]

6130

\[ {}y^{\prime } = \frac {y}{x}-\tan \left (\frac {y}{x}\right ) \]